Stiffness and damping in mechanical design - Rivin, Eugene I. (Marcel Dekker, 1999)
Offers designers and users of mechanical systems an overview of structural stiffness and damping and their critical roles in mechanical design. The text assesses the relationship between stiffness and damping parameters in mechanical systems and structural materials. An accompanying disk contains detailed analyses of stiffness- and damping-critical systems.